A Metabolic Immune Checkpoint: Adenosine in Tumor Microenvironment - Ohta, Akio (Frontiers in Immunology, 2016)
Within tumors, some areas are less oxygenated than others. Since their home ground is under chronic hypoxia, tumor cells adapt to this condition by activating aerobic glycolysis; however, this hypoxic environment is very harsh for incoming immune cells. Deprivation of oxygen limits availability of energy sources and induces accumulation of extracellular adenosine in tumors. Extracellular adenosine, upon binding with adenosine receptors on the surface of various immune cells, suppresses pro-inflammatory activities. In addition, signaling through adenosine receptors upregulates a number of anti-inflammatory molecules and immunoregulatory cells, leading to the establishment of a long-lasting immunosuppressive environment. Thus, due to hypoxia and adenosine, tumors can discourage anti-tumor immune responses no matter how the response was induced, whether it was spontaneous or artificially introduced with a therapeutic intention. Preclinical studies have shown the significance of adenosine in tumor survival strategy by demonstrating tumor regression after inactivation of adenosine receptors, inhibition of adenosine-producing enzymes or reversal of tissue hypoxia. These promising results indicate a potential use of the inhibitors of the hypoxia-adenosine pathway for cancer immunotherapy.